Factors Affecting Primary School Population and the Influence of Socialization Agents - Ugobueze, Ann Ngozi (Pusmedia Group Indonesia, 2024)
This article is motivated by the inequality of access to basic education caused by demographic factors (rural-urban migration), economic (poverty), cultural (gender discrimination), socialization (family and peer influence), and structural (unequal distribution of resources) which are interrelated and affect the level of participation and success of children's education in Nigeria. The primary aim of the present study is to understand how demographic, economic, cultural, policy, and environmental factors influence primary school populations, and how various socialization agents, including families, peers, media, schools, and government institutions, contribute to shaping children’s educational experiences. This research uses a theoretical review method by obtaining data from various sources of books, journals and so on. The study identifies key demographic trends such as birth rates, migration, and urbanization, as well as economic challenges like poverty and disparities in access to educational resources, that directly affect school enrollment patterns. Cultural attitudes toward education, gender roles, and government interventions, particularly in terms of policy and funding, further influence these dynamics. Additionally, health crises and access to sanitation are recognized as critical environmental factors impacting primary school populations. The study also looked into the role of socialization agents in influencing children’s educational decisions and retention. Families, particularly parents' educational background and socioeconomic status, play a significant role in shaping children’s educational trajectories. Peer influence, media representations of schooling, and the school environment itself are all important socialization forces that impact children's school choices, attitudes toward education, and retention. Moreover, community involvement and advocacy by local and national organizations are essential for fostering educational equity and inclusion. The study discusses the interplay between these socialization agents and how they contribute to school enrollment, retention, and overall educational equity. Despite the positive impact of these collaborations, several challenges persist, including socioeconomic disparities, cultural barriers, and institutional constraints. Finally, the paper offers policy recommendations aimed at improving primary school enrollment, strengthening the role of socialization agents, and promoting greater inclusivity and equity in primary education. This research pointed out the need for a collaborative approach to education that involves families, communities, schools, and policymakers in creating an equitable and accessible primary education system for all children